Effect of hot smoking on the quality of vimba (vimba vimba tenella) - Abdullah Diler; Behire Işıl Işıklı; Ahmet Güner; Yusuf Doğruer (Eurasian Journal of Veterinary Sciences)
In this investigation, it was aimed to determine the effects of hot smoking on the chemical, microbiological and organoleptical quality characteristics of Eğrez Fish (Vimbia vimbia tenella). For this purpose, the fish was dipped in brine (containing 17% NaCI) for twelve hours, and then they were smoked at 30C for 1/2 hour, and one hour at 50°C and atone hour at 80nC afterwards they were vacuum packaged and slored at 4 ±1° C, Smoked fish were analyzed for chemical, microbiological and organoleptical on the 7^. 14* 21=', 28th, and 43ra. On the other hand the fish were analyzed for determining some chemical and microbiological charactersitics before and after salting, important increases were seen in the ash and salt content and TBA value of fish after salting process (p<0,001, p<0.01}, Following the smoking process, moisture, fat, protein, and ash content of smoked fish showed differences in important degrees related to raw and salted fish (p<0.001, p<0.05). After salting process, it was determined that Micrococcus - Staphylococcus were increased (p<0.001) although total mesophilic aerobic and coliform bacteria count were decreased (pcO.OOl, p<0.05). Related to smoking process, total mesophilic aerobic count increased (p<0.001) eventhough Micrococcus- Staphylococcus and yeast-mould counts decreased (pcO.OOl). It was determined that sensory properties ol the samples were found acceptable to consume nearly 43 days period eventhough microbiological numbers of the samples were higher than values staled in the standard. In conclusion, with application of hot smoking process a product alternate to raw consume of Eğrez fish was obtained with different taste and aroma and stored safely at 4ºC for 43 days.